Indigenous people’s education, career aspirations, career choice and challenges among senior high school students in rural communities in Palawan - Andrea Josefa D. Perez; David R. Perez; Carolyn M. Illescas (International Journal of Education and Learning, 2021)
The study aims to determine the Indigenous people’s education, career aspirations, career choice, and challenges among senior high school students in rural communities in Palawan. The qualitative and quantitative methods used in the study. Mean, frequency counts, percentages, T-test, and Pearson Moment Correlation were employed. Results revealed that most of the parents had ages 39-44 years old, female, high school level, farmers, and earned below 1,000. As for ethnicity, most of them belong to the Palawan tribe, had 3-4 number of children, and a cash conditional transfer recipient. It also revealed that most of the learners had ages between 18-19 years old, female, Palawan, the first child in the family, enrolled under Technical Vocational and Livelihood, and traveled 5 kilometers distance of residence to the school. There is no significant relationship Between Parent-Respondents Profile and Career Aspirations of the Learners except in parents’ age. There is no significant Relationship Between Learner-Respondents Profile and their Career Aspirations except in age, sex, and track profile. There is no significant relationship between the demographic profile of the parents and the educational challenges except in parent’s occupation, cash conditional transfer recipient, and several children. There is no significant relationship between the learner’s demographic profile and the educational challenges except in distance from school, birth order, and sex. There is a significant difference between career aspirations among learners and their parents, while there is no significant difference between the career choice among indigenous learners and their parents and educational challenges among learners and parents.